The group as therapist - Chazan, Rachael, 1926- (International library of group analysis, 2001)
Annotation In this introductory text, Rachael Chazan describes the classic analytic group and demonstrates its potential benefits. She applies this classic analytic group model to schizophrenics, couples and multiple family groups, median groups and groups with psychotic and borderline personalities, using examples from her own extensive clinical experience.